Simplex-Centroid mixture design applied to arsenic (V) removal from waters using synthetic minerals. (15th May 2019) - Dias, Adriana Cristina; Fontes, Maurício Paulo Ferreira; Reis, Cesar; Bellato, Carlos Roberto; Fendorf, Scott
Abstract: Arsenic (As) is a toxic and carcinogenic element. Therefore, it is necessary to carry out research on As-contaminated water management in order to achieve the World Health Organization (WHO) standard for drinking water (0.010 mg L −1 ). A Simplex-Centroid mixture design (SCMD) was used to determine the best mineral composition for both maximum adsorption capacity of As(V) (MAC-As) and residual concentration of As(V) (RC-As), using synthetic poorly crystallized aluminum hydroxide (pAlHyd), calcined layered double hydroxide (cLDH), and two-line ferrihydrite (2ℓFh). The analysis of variance results and the predicted values of models showed a good agreement with the experimental data, indicating that SCMD is a reliable method to optimize As removal through determination of the best mineral composition. The ability of pure synthetic minerals to remove As from water was different among those mixtures thereof, which indicate that the mineral components interacted with each other. Results showed that cLDH was the best As adsorbent. However, it showed a RC-As higher than the WHO standard. The pAlHyd and 2ℓFh exhibited smaller MAC-As, but they lowered RC-As to below 0.010 mg L −1, showing no direct relationship between high MAC-As and low RC-As. Therefore, mineral compositions which combine high adsorption capacity with low residual concentration should work better for removing As from drinking water, ensuring it meets the WHO potability standard. Ternary diagrams for MAC-As and RC-As showed that the best combination for maximizing MAC-As and reducing RC-As should be a mixture of 75–90% of cLDH, 10–20% of pAlHyd, and 0–5% of 2ℓFh. Graphical abstract: Image 1 Highlights: Arsenic removal in synthetic minerals evaluated by mixture design method. Different ability in As removal using pure minerals or mixtures between them. New focus on evaluation of residual concentration of As (RC-As) in solution. Some adsorbents showed high adsorption capacity of As, however showed high RC-As. Low RC-As in solution is synonymous of water potability for human consumption.